Impacts of monocular, binocular, and functional visual acuity on vision-related quality of life in patients with type 2 diabetes - Kuo-Meng Liao (Nature Portfolio, 2021)
Abstract Although the association between visual acuity (VA) and vision-related quality of life (VRQoL) has been well reported in patients with type 2 diabetes mellitus (T2DM), little is known about how unilateral and bilateral VA affects daily performance in such patients. For this cross-sectional study, patients were recruited from the Diabetes Shared Care Network of the Division of Endocrinology and Metabolism, Zhong-Xiao Branch, Taipei City Hospital in Taiwan. Ninety patients with T2DM (51 men and 39 women) with a mean age of 60.3 ± 10.5 (standard deviation) years, 47% of whom had diabetic retinopathy, were included. The purposes were to compare the impacts of VA in the better eye, both eyes, and three forms of functional acuity scores (FAS) on VRQoL in patients with T2DM. VRQoL and corrected VA were assessed with the 25-item National Eye Institute Visual Function Questionnaire (NEI VFQ-25) and Early Treatment Diabetic Retinopathy Study (ETDRS) chart, respectively. Three FAS algorithms proposed by Colenbrander and the American Medical Association were used to assess FAS. Regression analyses were performed to determine the correlations among the five types of VA, the original composite scores, and the Rasch-calibrated composite scores of the NEI VFQ-25 on all patients with T2DM and on the same patients stratified by diabetic retinopathy (DR) and no-DR. The VA of both eyes had a higher impact on VRQoL and revealed a lower reduction estimated by the two forms of composite scores than did the VA of the better eye and three FAS algorithms (compared with binocular VA β estimates, − 14.5%, − 15.8%, − 29.3%, and − 11.8% for original composite scores, and − 16.1%, − 14.0%, − 24.6%, and 10.3% for Rasch-calibrated composite scores). When the T2DM group was stratified into DR and no-DR groups, significant associations between VA and VRQoL were observed only in the DR group. The VA of both eyes also had the greatest impact and reduction after stratification. The results indicated that unilateral better-eye VA and VA estimated by the three FAS algorithms seems to underestimate the impact of visual impairment on self-report VRQoL in patients with T2DM. This study provides empirical support for the importance of binocular VA assessment in regular clinical diabetes eye care.